2013
DOI: 10.1111/jdv.12246
|View full text |Cite
|
Sign up to set email alerts
|

Trichoscopy in Paediatric Patients with Tinea Capitis: A Useful Method to Differentiate from Alopecia Areata

Abstract: Broken and dystrophic hairs, corkscrew hairs, comma hairs and black dots were observed only in patients with TC; yellow dots, exclamation mark hairs and vellus hairs were observed only in patients with alopesi areata. Further studies with larger numbers of patients are needed to determine specific trichoscopic findings of TC and to access differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
66
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 16 publications
21
66
0
7
Order By: Relevance
“…However, it is also present in the acute form of alopecia areata . Yellow dots were observed in 6–100% (mean value, 62%) of patients with alopecia areata . Differences in the reported frequency of this trichoscopic finding may be attributed to skin phototypes (it has been hypothesized that yellow dots are generally less visible in populations with yellowish or dark color of the skin), type of dermoscopy device, as well as different shampooing habits between European, Asian and Latin American cultures .…”
Section: Trichoscopic Findings In Alopecia Areatamentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also present in the acute form of alopecia areata . Yellow dots were observed in 6–100% (mean value, 62%) of patients with alopecia areata . Differences in the reported frequency of this trichoscopic finding may be attributed to skin phototypes (it has been hypothesized that yellow dots are generally less visible in populations with yellowish or dark color of the skin), type of dermoscopy device, as well as different shampooing habits between European, Asian and Latin American cultures .…”
Section: Trichoscopic Findings In Alopecia Areatamentioning
confidence: 99%
“… The ranges from published articles are given for the trichoscopic features for which the frequency was evaluated. ‡ Mean value was calculated by dividing the total number of patients with a particular feature by the total number of patients in studies reporting the frequency of this feature. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Amer et al [39] reported that the most frequent dermoscopic feature of tinea capitis in an Egyptian population was comma hairs, first described by Slowinska et al [40], followed by zigzag hairs, found in 60 and 30% of their patients, respectively. Other features of tinea capitis reported in black scalp include black dots, hair casts, broken hairs, clip or question mark hairs, and Morse codeshaped hair [4,34,39,41]. Trichotillomania Few reports have been published about the trichoscopic characteristics of trichotillomania in dark skin [26,[42][43][44].…”
Section: Tinea Capitismentioning
confidence: 99%
“…Bu yöntemler arasında özellikle trikoskopinin saç hastalıklarında kullanımı ile ilgili son yıllarda çokça yayın göze çarpmaktadır (15)(16)(17). Non invazif olan bu yöntem, oldukça değerlidir.…”
Section: Discussionunclassified